IMPLEMENTASI KURIKULUM 2013 (K13) SMP NEGERI 2 SAROLANGUN - YAHFENEL EVI FUSSALAM; ELMIATI - (Jurnal Muara Pendidikan, 2018)
This study investigated implementation Curriculum 2013 (K 13) at SMP Negerii 2 Sarolangun. It aimed at analyzing implementation of K 13 and identifying the factors influenced implementation K 13. Descriptive method with three main instruments; observation, interview and documentation were used to collect data. The finding showed that SMP Negeri 2 Sarolangun was applied K 13 through socialization, teacher preparation, and giving facilitation. The factors influence K 13 divided into two factors, they were supporting factors and problematic factors. As conclusion, all components includes government, school, teacher, parents, students, and stake holder should be interest and support the implementation K 13 at SMP Negeri 2 Sarolangun